Lisdexamfetamine Dimesylate for the Treatment of Attention Deficit Hyperactivity Disorder in Adults With a History of Depression or History of Substance Use Disorder - Kollins, Scott H. (Matrix Medical Communications, 2011)
Objective: To evaluate the efficacy and safety of lisdexamfetamine dimesylate in participants with attention deficit hyperactivity disorder and a history of depression and/or substance use disorder. History of these comorbidities was recorded from medical history forms completed by the study clinicians. Design/Setting: An exploratory, post-hoc analysis was conducted using data from a randomized, double-blind, placebo-controlled, forced-dose titration study of lisdexamfetamine dimesylate. Participants: Adults with attention deficit hyperactivity disorder. Measurements: Changes in Attention Deficit Hyperactivity Disorder Rating Scale IV total scores and Clinical Global Impressions-Improvement scale were used to evaluate the efficacy of lisdexamfetamine dimesylate. The incidence of treatment-emergent adverse events was also evaluated. Results: The intention-to-treat population included 36 participants with a history of depression and 17 participants with a history of substance use disorder. Mean changes in Attention Deficit Hyperactivity Disorder Rating Scale IV and Clinical Global Impressions-Improvement from baseline to endpoint for these subpopulations were similar to those of participants without a history of depression and/or history of substance use disorder. Lisdexamfetamine dimesylate was generally well tolerated in all subgroups. Conclusion: The response to lisdexamfetamine dimesylate and the treatment-emergent adverse event profiles of participants with a history of depression and/or a history of substance use disorder were similar to those of participants with no history of these disorders. Larger studies that prospectively enroll participants with attention deficit hyperactivity disorder and these comorbid disorders are needed to more conclusively evaluate the safety and efficacy of stimulant treatment in these populations.